La educación y los riesgos de exclusión social para los escolares de familias inmigrantes en Portugal y España - Raquel Poy (Instituto Politécnico de Bragança, 2018)
From the statistical analysis of the risk scenarios of social exclusion that migration can currently show in Spain and Portugal, the risk scenarios faced by schoolchildren from immigrant families in relation to different educational policy approaches are reviewed. Official data indicates that immigrant status represents a risk of higher probability of educational failure, lower level of education at the end of schooling and lower employability. From an inclusive and intercultural approach, reference is made to successful cases in the approach to this problem in Spain, such as the experiences developed in the last two decades of the Learning Communities and the promising evolution of performance in Portugal shown by the OECD assessment tools. .